2020
DOI: 10.3390/ijms21249735
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Adenocarcinomas and Signet-Ring Cell Carcinoma: Unraveling Gastric Cancer Complexity through Microbiome Analysis—Deepening Heterogeneity for a Personalized Therapy

Abstract: Gastric cancer (GC) is the fifth most prevalent cancer worldwide and the third leading cause of global cancer mortality. With the advances of the omic studies, a heterogeneous GC landscape has been revealed, with significant molecular diversity. Given the multifaceted nature of GC, identification of different patient subsets with prognostic and/or predictive outcomes is a key aspect to allow tailoring of specific treatments. Recently, the involvement of the microbiota in gastric carcinogenesis has been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…• The results demonstrated significant differences in the microbial profile and composition between early gastric cancer and advanced gastric cancer Ravegnini et al 2020 • 10 adenocarcinoma and 10 signet-ring cell carcinoma and their paired non-tumor counterparts…”
Section: Authors Year Sample Size Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…• The results demonstrated significant differences in the microbial profile and composition between early gastric cancer and advanced gastric cancer Ravegnini et al 2020 • 10 adenocarcinoma and 10 signet-ring cell carcinoma and their paired non-tumor counterparts…”
Section: Authors Year Sample Size Resultsmentioning
confidence: 94%
“…A recent study gave insight into the microbial composition in different subtypes of GC. Fusobacteria, Bacteroidetes, Patescibacteria were enriched in signet-ring cell carcinoma, whereas Proteobacteria and Acidobacteria were enriched in adenocarcinoma (Ravegnini et al, 2020). Dysbiosis of the oral microbiome has been linked to inflammatory bowel disease, colorectal cancer, and pancreatic cancer (Nakatsu et al, 2015;Atarashi et al, 2017;Gaiser et al, 2019).…”
Section: Authors Year Sample Size Resultsmentioning
confidence: 99%
“…In a previous study, using a magnetically controlled sampling capsule endoscope (MSCE), a dramatic decrease in the abundance of Bacteroidetes , Patescibacteria , and Actinobacteria was detected in the antibiotic-induced diarrhea model [ 50 ]. In contrast, the microbiota composition in signet-ring cell carcinoma (SRCC) tumor samples was significantly enriched in the phyla Fusobacteria, Bacteroidetes , and Patescibacteria [ 51 ]. The phylum Patescibacteria was enriched throughout the luminal content in the small intestine when compared with that of the colon of preterm lambs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Patescibacteria was significantly enriched in the group with alcoholic liver disease compared to the control, treatment, and positive groups [ 38 ]. Another research study also reported that the abundance of Patescibacteria was elevated in the signet-ring cell carcinoma patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%